Permasalahan Dan Penanganan Masalah Bullying Pada Anak Usia Sekolah - Austie, Leony; Elsa Restu Aulia; Marni Hariati; Romiaty Romiaty (IHSANIKA : Jurnal Pendidikan Agama Islam, 2025)
Bullying in elementary schools is a serious issue that negatively impacts children’s physical, psychological, and social development. This study aims to identify the forms of bullying, its causal factors, the resulting impacts, and the handling efforts that can be implemented in elementary schools. The method used is a literature review by examining various relevant scientific sources. The findings indicate that bullying is influenced by factors such as children's temperament, family communication patterns, and an unconducive school environment. The impacts of bullying are highly detrimental to victims, including anxiety, decreased academic achievement, trauma, and even suicidal ideation, and also have negative effects on the perpetrators. Effective handling efforts involve the active roles of teachers, parents, and the school through character education, instilling religious values, empathetic communication, and emotional approaches. The implications of this study emphasize the importance of collaboration among all parties to create a safe, comfortable, and supportive school environment for optimal child development.